EL APOYO POLÍTICO-DIPLOMÁTICO Y ECONÓMICO DE ARGENTINA A ITALIA EN LA INMEDIATA POSGUERRA (1946-1947) CONTADO POR LA PRENSA ITALIANA - Pizzoni, Gemma (Cultura Latinoamericana, 2021)
This article aims to piece together the economic and diplomatic relations between Italy and Argentina during the Second post- World War through the narration of the Italian press. The research considers the information of some Italian newspapers and journals, selected for their ideological leaning: the affiliated organizations of a party, the independent press, printed especially in the North of Italy, and the catholic one. Even if after World War II Italy and Argentina had opposite economic, political, and social contests, they developed some important contact points, not only for their own domestic policies, but also for the international relations. The article analyzes how the selected Italian press illustrates some common meeting points, particularly for the biennium 1946-1947: the food supplies from the platense republic at the impoverished and destroyed peninsula, the argentine support at the Paris Peace Conference for a fair peace treaty for Italy and the diplomatic missions organized from both two nations.